Genetic and phenotypic variation of the malaria vector Anopheles atroparvus in southern Europe - Vicente, J.L.; Carla A. Sousa; Alten, B.; Caglar, S.S.; Falcutá, E.; Latorre, J.M.; Toty, C.; Barré, H.; Demirci, B.; Di Luca, M.; Toma, L.; Alves, R.; et al. (Malaria Journal, 2011)
Background There is a growing concern that global climate change will affect the potential for pathogen transmission by insect species that are vectors of human diseases. One of these species is the former European malaria vector, Anopheles atroparvus. Levels of population differentiation of An. atroparvus from southern Europe were characterized as a first attempt to elucidate patterns of population structure of this former malaria vector. Results are discussed in light of a hypothetical situation of re-establishment of malaria transmission. Methods Genetic and phenotypic variation was analysed in nine mosquito samples collected from five European countries, using eight microsatellite loci and geometric morphometrics on 21 wing landmarks. Results Levels of genetic diversity were comparable to those reported for tropical malaria vectors. Low levels of genetic (0.004